Functional Promiscuity of Homologues of the Bacterial ArsA ATPases. (19th September 2010) - Castillo, Rostislav; Saier, Milton H.
Abstract : The ArsA ATPase of E. coli plays an essential role in arsenic detoxification. Published evidence implicates ArsA in the energization of As(III) efflux via the formation of an oxyanion-translocating complex with ArsB. In addition, eukaryotic ArsA homologues have several recognized functions unrelated to arsenic resistance. By aligning ArsA homologues, constructing phylogenetic trees, examining ArsA encoding operons, and estimating the probable coevolution of these homologues with putative transporters and auxiliary proteins unrelated to ArsB, we provide evidence for new functions for ArsA homologues. They may play roles in carbon starvation, gas vesicle biogenesis, and arsenic resistance. The results lead to the proposal that ArsA homologues energize four distinct and nonhomologous transporters, ArsB, ArsP, CstA, and Acr3.